Nigeria public expenditure review : march 18, 1996 - World Bank; West Central Africa Department; World Bank (Washington, D. C. : World Bank, 1996)
Nigeria's tremendous potential for growth and poverty reduction has yet to be fulfilled. A key constraint has been the recent conduct of macroeconomic, particularly fiscal policies. These have led to rising inflation, falling growth, and declining real incomes.
Includes bibliographical references p. 249- 251.
hza 12/02/2019
Loans
Keywords: Economic planning; Economic policy; Nigeria